Evaluation and Analysis of Push-Pull Cable Actuation System Used for Powered Orthoses - Grosu, Svetlana; Rodriguez–Guerrero, Carlos; Grosu, Victor; Vanderborght, Bram; Lefeber, Dirk (Frontiers in Robotics and AI, 2018)
Cable-based actuation systems are preferred in rehabilitation robotics due to their adequate force transmission and the possibility of safely locating the motors away from the patient. In such applications, the cable dynamics represents the prescribing component for the system operating loads and control. A good understanding of the actuation, based on cable-conduit transmission, is therefore becoming mandatory. There are several types of cable-conduit configurations used for the actuation. Currently, there is lack of information in literature with regard to the push-pull cable type. Therefore the main focus of this contribution is to evaluate push-pull cable-based actuation used within wearable robotic devices. This study includes working principle description of push-pull cable actuation with its characteristic advantages and drawbacks.The use of push-pull cables in bidirectional force transfer with remote actuation is investigated being integrated in a test-stand setup of a novel gait rehabilitation device.The experimental results and close analysis of the push-pull cable-based actuation system outline its performance, the overall dynamic behavior and the transmission effectiveness for a powered orthoses.